New Flexible Protective Coating for Printed Smart Textiles - Valérie Bartsch; Volkmar von Arnim; Sven Kuijpens; Michael Haupt; Thomas Stegmaier; Götz T. Gresser (Applied Sciences, 2021)
In the field of food packaging, the addition of exfoliated layered silicates in polymers has been established to improve the polymers’ gas barrier properties. Using these polymers as coatings to protect smart textiles from oxidation and corrosion while maintaining their textile properties should significantly extend their lifetime and promote their market penetration. The aim of this study was to print new polymer dispersions containing layered silicates to protect screen-printed conductive structures, and to test the resulting samples. For this, appropriate printing parameters were determined by statistical design of experiments. According to these results, conductive structures were printed and protected with the selected coating. The abrasion resistance and the continuity of the protective layer of the printed samples were then measured. A continuous protective coating of approximately 70–80 µm thickness was applied on a conductive structure. The printed samples showed a very high resistance to abrasion (unchanged by 85,000 abrasion cycles) while remaining flexible and presenting a lower water vapor permeability (<2.5 g/m² d) than the coatings commonly used in the textile field.